(untitled) (Orinoquia, 2024)
Whey is a liquid byproduct of milk coagulation and one of the largest byproducts in the dairy industry. To produce 1 to 2 kg of cheese, 10 kg of milk is used, generating 8 to 9 kg of whey as a byproduct. It is forecasted that by 2050, the population will increase by 26%, which will lead to a significant rise in cheese consumption, thus increasing whey production. The aim of this review is to identify the amount of whey produced in Colombia, its main characteristics, and explore various alternatives for hydrogen production from whey, such as dark fermentation, photofermentation, and microbial electrolysis cells, along with their key variables and respective microorganisms. This allows for the determination that integrated processes are one of the most promising alternatives, as pathways like photofermentation and microbial electrolysis cells do not yield optimal results unless combined with other biological mechanisms.